Effect of Clove Powder and Modified Atmosphere Packaging on the Oxidative and Sensory Quality of Chicken Meat Caruncles During Ambient Storage (35±20C) Conditions - Singh, Parminder; Sahoo, Jhari; Chatli , K. Manish; Biswas, Ashim K. (Journal of Meat Science, 2014)
The individual as well as synergistic effect of modified atmosphere packaging and clove powder as natural preservative on the oxidative and sensory quality of chicken meat caruncles during storage at 35±2°C at 70% R.H. for 60 days was evaluated. For this, four different batches of chicken meat caruncles were prepared i.e. CA (control, aerobic packaging), CMAP (Control, 50:50 CO2 /N2 modified atmosphere packaging), TA (treated with 0.2% clove powder, aerobic packaging) and TMAP (treated with 0.2% clove powder, 50:50 CO2/N2 modified atmosphere packaging). In oxidative quality, TBARS value of TMAP sample was significantly lower (P
Keywords: Chicken meat caruncles; Clove powder; Modified atmosphere packaging; Oxidative quality